Characterization of upper respiratory tract isolates from children with recurrent tonsillitis (Research, Society and Development, 2021)
To analyze the profile of airway Upper Respiratory Tract isolates from children with recurrent tonsillitis. Samples were taken using nasal cavity, oropharynx and nasopharynx swabs from30 children called the test group before tonsillectomy. Counting, isolation, identification and sequencing of the 16S rRNA, biofilm production and antimicrobial sensitivity investigation were performed. Staphylococcus aureus (S. aureus) was the only microorganism recovered in 36.6% of patients, being more present in the oropharynx and with greater resistance to erythromycin 95%, penicillin 85% and cefoxitin 85%. All isolates were formed by biofilm, 20% formed by strongly adherent biofilm. S. aureus resistant and biofilm formed, were isolated in the three studied sites, suggesting that this species contributes to recurrent tonsillitis. Impact of the study: The ability of S. aureus to acquire resistance and its other associated factors such as biofilm formation, can make this microorganism recover more easily in the microbiota of patients, taking into account the other microorganisms present there after the use of antibacterial.